2020
DOI: 10.1128/jcm.01465-20
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Serotyping, Clinical Manifestations, and Antimicrobial Resistance of Nontyphoidal Salmonella Gastroenteritis in Hospitalized Children in Ho Chi Minh City, Vietnam

Abstract: Nontyphoidal Salmonella (NTS) are among the most common aetiological agents of diarrhoeal diseases worldwide and have become the most commonly detected bacterial pathogen in children hospitalised with diarrhoea in Vietnam. Aiming to better understand the epidemiology, serovar distribution, antimicrobial resistance (AMR), and clinical manifestation of NTS gastroenteritis in Vietnam, we conducted a clinical genomics investigation of NTS isolated from diarrheal children admitted to one of three tertiary hospitals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 49 publications
2
33
1
Order By: Relevance
“…Additionally, cephalosporins are a commonly used antimicrobial class in Vietnam [ 6 ] and we detected bla CMY , bla SHV, and bla TEM in the fecal samples. More specifically, we identified bla CTX-M , a group of ESBL genes that have been commonly found in a range of enteric pathogens, including Shigella and Salmonella [ 12 , 34 ], in several samples from young children. The diversity of AMR genes identified corroborates with a previous study conducted in untreated sewage from countries with different economic backgrounds, which concluded that the global distribution of AMR genes is not only dependent on the socioeconomic status of each country, but also that Vietnam is one of the countries with the most divergent distribution of AMR genes [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, cephalosporins are a commonly used antimicrobial class in Vietnam [ 6 ] and we detected bla CMY , bla SHV, and bla TEM in the fecal samples. More specifically, we identified bla CTX-M , a group of ESBL genes that have been commonly found in a range of enteric pathogens, including Shigella and Salmonella [ 12 , 34 ], in several samples from young children. The diversity of AMR genes identified corroborates with a previous study conducted in untreated sewage from countries with different economic backgrounds, which concluded that the global distribution of AMR genes is not only dependent on the socioeconomic status of each country, but also that Vietnam is one of the countries with the most divergent distribution of AMR genes [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, MDR Salmonella species are also widely disseminated in Vietnamese pigs (5,8), poultry (13), seafood (5), and humans (41). In our study, 69% of the strains were MDR, and S. Derby carried more ARGs than S. Rissen.…”
Section: Discussionmentioning
confidence: 46%
“…FosA was included recently in the Resfinder database, which determines the importance of keeping track of the updates of public databases (43). No ESBL-and AmpC-producing isolates were detected in our study, whereas in other published studies in Vietnam, such strains were also detected in pigs (5) and in humans (41). One isolate carried mcr-1 (Table 3), which was also detected in Vietnamese pigs (8) and poultry samples (14).…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations